2019
DOI: 10.4085/1062-6050-54.082
|View full text |Cite
|
Sign up to set email alerts
|

Concepts Important to Secondary Prevention of Posttraumatic Osteoarthritis

Abstract: oint injuries occur when primary prevention fails or the joint is subjected to overwhelming forces. Although the incidence of noncontact anterior cruciate ligament (ACL) injuries can likely be reduced, ACL tears will continue to occur due to accidents, contact sports, falls, and any number of unpredictable situations resulting in knee trauma. Thus, a substantial role remains for improving patients' surgical and rehabilitative outcomes in the aftermath of ACL tears. To achieve these goals, validated and appropr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 17 publications
0
4
0
1
Order By: Relevance
“…Therefore, our synthesis of the available studies indicates limited evidence of a difference between ACLR and rehabilitation compared to conservative management on the incidence of PTOA after ACL injury. Research indicates surgery may provide benefits by improving joint stability and reducing the risk of a secondary injury such as meniscal tears (Chu, 2019). There is also conflicting evidence that surgery may exacerbate and prolong the intraarticular inflammatory response, subsequently increasing the risk of PTOA (Thomas et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, our synthesis of the available studies indicates limited evidence of a difference between ACLR and rehabilitation compared to conservative management on the incidence of PTOA after ACL injury. Research indicates surgery may provide benefits by improving joint stability and reducing the risk of a secondary injury such as meniscal tears (Chu, 2019). There is also conflicting evidence that surgery may exacerbate and prolong the intraarticular inflammatory response, subsequently increasing the risk of PTOA (Thomas et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Профилактика ХПТБ заключается в эффективном купировании острой боли, подавлении локального воспаления и замедлении развития дегенеративных процессов [90].…”
Section: посттравматическая боль: терапевтические подходыunclassified
“…8 Quantitative magnetic resonance imaging (MRI) relaxation mapping has been primarily validated for articular cartilage tissue. [62][63][64] In addition to the research presented at ACL Research Retreat VIII, including the use of novel MRI ultrashort echo time T2* to evaluate healing ACL grafts, 21,65 T2* relaxation has been used to study animal ACL grafts 66,67 and has been negatively associated with the yield load of healing ACL grafts. 66 Additionally, these imaging sequences have been used to evaluate the structural characteristics of the Achilles 68 and patellar 69 tendons.…”
Section: Tertiary Preventionmentioning
confidence: 99%
“…Mounting evidence suggests that the progression to PTOA is influenced by the interplay between aberrant joint biomechanics and altered joint tissue metabolism after injury. 126,[159][160][161][162] Work reflecting more than a decade of longitudinal study 21,163 of ACL-injured patients at the University of Pittsburgh and Stanford University presented by keynote speaker Constance Chu, MD, showed that approximately half of patients had quantitative MRI ultrashort echo time-T2*, mechanical, or biological markers indicating a higher OA risk just 2 years after ACLR. Several researchers sought to characterize the effects of early structural, biomechanical, and biological changes after ACL injury and their association with important outcomes related to joint health status over time (Blackburn abstract #29, Pfeiffer abstract #30, Wallace abstract #31, and Trump abstract #32).…”
Section: Development and Progression Of Ptoamentioning
confidence: 99%
See 1 more Smart Citation